2007
DOI: 10.1128/jvi.02693-06
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-Associated Virus Type 2 p5 Promoter: a Rep-Regulated DNA Switch Element Functioning in Transcription, Replication, and Site-Specific Integration

Abstract: The large Rep proteins, p68 and p78, function as master controllers of the adeno-associated virus type 2 (AAV2) life cycle, involved in transcriptional control, in latency, in rescue, and in viral DNA replication. The p5 promoter may be the nucleic acid complement to the large Rep proteins. It drives expression of the large Rep proteins, it undergoes autoregulation by Rep, it undergoes induction by helper virus, it is a target substrate for Rep-mediated site-specific integration (RMSSI), and it can function as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…5E). In addition to the ITR, the p5 promoter has been shown to contain a functional RBS/TRS, and in plasmid systems, the p5 promoter is able to independently enhance AAVS1 integration efficiency (13,38,39,62). The combination of a p5 transcriptional complex localized near the leftend ITR may present a unique structural domain to specifically interact with the integration complex forming on a genomic site.…”
Section: Discussionmentioning
confidence: 99%
“…5E). In addition to the ITR, the p5 promoter has been shown to contain a functional RBS/TRS, and in plasmid systems, the p5 promoter is able to independently enhance AAVS1 integration efficiency (13,38,39,62). The combination of a p5 transcriptional complex localized near the leftend ITR may present a unique structural domain to specifically interact with the integration complex forming on a genomic site.…”
Section: Discussionmentioning
confidence: 99%
“…This primarily drives the expression of Rep proteins as well as cellular factors such as YY1, a human GLI-Kruppel-related protein [21,133]. Both P5 and P19 promoters act as a switch element involved in transcription, replication, and site-specific integration [134,135]. The activation of these promoters leads to the generation of Rep78, Rep68, Rep 52 and Rep 40.…”
Section: Gene Expression and Replicationmentioning
confidence: 99%
“…These studies also indicated that the TATA box flanking the Rep binding site was absolutely required for in vivo replication of the p5 element, likely through TATA binding protein-mediated enhancement of Rep-dependent binding and nicking. Similarly, Murphy et al recently confirmed that mutating the TATA box severely compromised replication of the p5 region and also found that RMSSI of p5-containing plasmids was sensitive to the same mutations as those affecting replication of this element (7). However, these studies, like the previous ones, were performed by analyzing stable cell clones derived from actively dividing cells, such as HeLa or 293 cells, transfected with p5-containing plasmids.…”
mentioning
confidence: 70%
“…A first study was conducted to determine if the minimal 55-bp p5 element, identified as an efficient replication origin (3), was also able to increase RMSSI of rAAV plasmid as previously documented for the entire p5 region. To answer this question, we used the procedure that was previously employed by other investigators (7,10,11), consisting of the analysis of stable cell clones isolated from HeLa cells transfected with the rAAV plasmid containing different versions of the p5 element inserted between the ITRs (Fig. 1).…”
mentioning
confidence: 99%